POTRET KEPEMIMPINAN SANTRI PUTRI ANNUQAYAH - mainnah, Muth (Pusat Studi Gender dan Anak LPPM UIN Sunan Ampel Surabaya, 2013)
Leader is someone who is mandated to carry out the task ofÂ leadership. Being a leader is the right ofÂ everyindividual, regardless ofÂ the sex. History and tafsir (Qurâanic exegesis) that are shaped and formed bypeople in the past have raised paradigm on who women are too weak to be leaders. It is quite often that historyis dishonestÂ against women. Consequently, theÂ position of women is seen as limited in the name of herbiological aspect. Neverthelles, womenâs potentials are gaining slowly the attention and the acknowledgement.The receive public acknowledging their potentials even to become leader in the public sphere.Â Interestingly,Pesantren where gender is still considered as taboo turn out to have given the acknowledgement on womenâspotentials. Eventhough Pesantren applies male-female segregation, it optimalizes the potentials of bothmale dan female santriâs. In this segregated system, female students (santriwati) are allowed room andopportunity to practice skills as leaders, assisting the Pesantren leader to teach and to assist the students andPesantren affairs.Â So, despite the fact that it still applies some traditional systems, Pesantren indeed hasallowed rooms for women to be leaders.